POPULATION STRUCTURE OF Hoya spp. (APOCYNACEAE: ASCLEPIADOIDEAE) AT BODOGOL NATURE-CONSERVATION EDUCATION CENTER, INDONESIA - Jessica Elfani Bermuli; Sulistijorini Sulistijorini; Sri Rahayu (SEAMEO BIOTROP, 2019)
Hoya species are epiphytic flowering plants known for their traditional medicinal value. Since 2011, eight Hoya species have been recorded at the Bodogol Nature-Conservation Education Center (BNCEC), Bogor, Indonesia. To support effective conservation measures, this study aimed to analyze the population structure and distribution patterns of Hoya species at BNCEC. Data were collected from July to August 2016 using a purposive sampling method within a 400 m² plot. The results showed that population structures varied among species. The population structure of H. multiflora formed an inverted pyramid, with more adult individuals than seedlings and juveniles. Both H. campanulata and H. imperialis exhibited a natural population pyramid, indicating a balanced proportion of seedlings, juveniles, and adults. H. lacunosa showed an hourglass-shaped structure, in which the numbers of seedlings and adults were higher than juveniles. H. hasseltii and H. vitellinoides did not display clear population structures because no adult individuals were observed. The distribution pattern of Hoya populations at BNCEC was clumped, as indicated by Morisita’s index (0.661).